Poly(I:C) Potentiates T Cell Immunity to a Dendritic Cell Targeted HIV-Multiepitope Vaccine - Apostólico, Juliana de Souza; Lunardelli, Victória Alves Santos; Yamamoto, Marcio Massao; Cunha-Neto, Edecio; Boscardin, Silvia Beatriz; Rosa, Daniela Santoro (Frontiers in Immunology, 2019)
Cellular immune responses are implicated in resistance to HIV and have been considered for the development of an effective vaccine. Despite their safety profile, subunit vaccines need to be delivered combined with an adjuvant. In the last years, in vivo antigen targeting to dendritic cells (DCs) using chimeric monoclonal antibodies (mAb) against the DC endocytic receptor DEC205/CD205 was shown to support long-term T cell immunity. Here, we evaluated the ability of different adjuvants to modulate specific cellular immune response when eight CD4+ HIV-derived epitopes (HIVBr8) were targeted to DEC205+ DCs in vivo. Immunization with two doses of αDECHIVBr8 mAb along with poly(I:C) induced Th1 cytokine production and higher frequency of HIV-specific polyfunctional and long-lived T cells than MPL or CpG ODN-assisted immunization. Although each adjuvant elicited responses against the 8 epitopes present in the vaccine, the magnitude of the T cell response was higher in the presence of poly(I:C). Moreover, poly(I:C) up regulated the expression of costimulatory molecules in both cDC1 and cDC2 DCs subsets. In summary, the use of poly(I:C) in a vaccine formulation that targets multiple epitopes to the DEC205 receptor improved the potency and the quality of HIV-specific responses when compared to other vaccine-adjuvant formulations. This study highlights the importance of the rational selection of antigen/adjuvant combinations to potentiate the desired immune responses.